Domination in Iterated Prisoner's Dilemma - Brown, Joseph Alexander; Ashlock, Daniel A. (2011 24th Canadian Conference on Electrical and Computer Engineering(CCECE), 2011)
Domination is a concept in Game Theory which has not been fully explored in the Iterated Prisoner's Dilemma. The idea of domination has previously been restricted to current moves looking at a single game and not a sequence of moves. An extension of the notion of domination is made that allows for the formalization of various behaviours exhibited in agents playing IPD. This formalization organizes behaviours such as "nice" into sets of dominated agents in an elegant fashion. In this initial study, we focus on dominators for sets of agents drawn from the set: Always Cooperate, Always Defect, and Tit-for-Tat.